[PP.15.32] NEW MODEL TO INVESTIGATE THE INFLUENCE OF AIRCRAFT NOISE IN THE PATHOPHYSIOLOGICAL CONCEPT OF HYPERTENSION. (September 2017) - Jumar, A.; Ott, C.; Harazny, J.M.; Striepe, K.; Karg, M.V.; Schmieder, R.E.
Abstract : Objective: Epidemiological studies have found a link between aircraft noise exposure and increased incidence of arterial hypertension and thus cardiovascular disease. The underlying pathophysiological mechanisms are not yet fully understood. The kidney acts as a long-term regulator of blood pressure and controls the extracellular sodium and water balance. Animal work and clinical studies show that mental stress affects the renal plasma flow and central hemodynamics. Design and method: We could establish a model to analyse the influence of 30 minutes standardized aircraft noise with a maximal sound pressure level of 80 dB on renal and central hemodynamics in 80 healthy volunteers. Renal hemodynamics were investigated using the clearance analysis with infusion of paraaminohippuric acid (PAH) and Inulin. Central hemodynamics were analysed using cardio impedance tomography. Results: Cardio impedance tomography showed no difference in RR-ECG duration (978 ± 143 vs. 907 ± 199 ms, p = 0.072), heart frequency (63 ± 9 vs 66 ± 10 bpm, p = 0.130), cardiac index (3.3 ± 0.65 vs 3.5 ± 0.82 l/min/m 2, p = 0.330) and total peripheral resistance index (2031 ± 622 vs 2032 ± 655, p = 0.998) in persons after noise exposure compared to sham exposed individuals. There were no significant differences in renal plasma flow (698 ± 124 vs. 693 ± 123 ml/min, p = 0.215) and glomerular filtration rate (152 ± 19 vs 151 ± 18 ml/min, p = 0.626) between noise and sham exposed individuals. There was an increase in renal plasma flow between baseline (688 ± 120 ml/min) and noise exposure (698 ± 124 ml/min, p = 0.011). Conclusions: We established a model to investigate the influence of aircraft noise on renal and central hemodynamics. In healthy individuals there was no change in central hemodynamics caused by short term aircraft noise exposure. Renal plasma flow increased between baseline and noise exposure, possibly pointing to a change in renal hemodynamics. We plan to extend our population to 44 hypertensive patients.